Aerosol Effects on Instability, Circulations, Clouds, and Precipitation - Seoung-Soo Lee; Wei-Kuo Tao; Chang-Hoon Jung (Advances in Meteorology)
It is well known that increasing aerosol and associated changes in aerosol-cloud interactions and precipitation since industrialization have been playing an important role in climate change, but this role has not been well understood. This prevents us from predicting future climate with a good confidence. This review paper presents recent studies on the changes in the aerosol-cloud interactions and precipitation particularly in deep convective clouds. In addition, this review paper discusses how to improve our understanding of these changes by considering feedbacks among aerosol, cloud dynamics, cloud and its embedded circulations, and microphysics. Environmental instability basically determines the dynamic intensity of clouds and thus acts as one of the most important controls on these feedbacks. As a first step to the improvement of the understanding, this paper specifically elaborates on how to link the instability to the feedbacks.